The Effect of Budget Participation on Budget Weapons - Sahmin Noholo; Ayu Rakhma Wuryandini (Journal of International Conference Proceedings (JICP), 2018)
The purpose of this study was to examine the relationship between: budgetory participative to budgetary slack. This type of research is classified as causative research. The population in this research is SKPD in Kabupaten Gorontalo. The sampling technique by purposive sampling with the consideration of the budget compilers is burdened with budget targets in completion of his duties and has occupied his position at least five years. Samples taken are All ranks that participate and responsible in the process of preparing the budget for the unit he leads that each Head of SKPD and Head of sub-finance who participated in the preparation of SKPD budget consists of 20 SKPD Regional District of Gorontalo. Respondents in this study amounted to 50 people. Of the 50 questionnaires submitted there were 39 people (78%) who participated in the study and sent back their answers. After data editing and preparation for processing data as much as 3 (7.69%) can not be used because of incomplete and empty questionnaire filling. So the questionnaire that can be used as data in this research amounted to 36 pieces (70.31%).The analytical method used is linear regression analysis, where budget slack as dependent variable and independent variable is budget participative. The result of this research is budget participative variable do not have significant influence to budget slack variable. Keywords: Budgetary Participation; slack Budget; Gorontalo Districts